2006
DOI: 10.1097/00004703-200604002-00007
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Autism Spectrum Disorders With the Social Communication Questionnaire

Abstract: The Social Communication Questionnaire (SCQ) is a parent report screening measure for autism spectrum disorders (ASDs) based on the Autism Diagnostic Interview-Revised (ADI-R). To examine its validity in a young sample, the SCQ was given to parents of 151 children at a mean age of 5 years, before assessment in tertiary autism or preschool clinics. Overall sensitivity was .71, the same for both clinics, but specificity was better for the preschool clinic (.62) than for the autism clinic (.53) reflecting fewer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 13 publications
4
150
0
9
Order By: Relevance
“…Isso deixa claro que a aplicação do questionário e do protocolo de adaptação sócio-comunicativa a diferentes informantes pode fornecer um resultado bastante homogêneo, sendo possível realizar de forma fidedigna a caracterização das habilidades de relacionamento social dessas crianças. Esses dados são compatíveis com as idéias de diversos autores (12)(13)(14)(15)(16) no sentido de que a consideração da perspectiva dos pais de crianças do espectro autístico quanto ao comportamento linguístico, cognitivo e social de seus filhos merece destaque, possibilitando que estes se tornem parceiros dos profissionais envolvidos no processo de intervenção, ajudando no monitoramento do nível de desenvolvimento destas crianças.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Isso deixa claro que a aplicação do questionário e do protocolo de adaptação sócio-comunicativa a diferentes informantes pode fornecer um resultado bastante homogêneo, sendo possível realizar de forma fidedigna a caracterização das habilidades de relacionamento social dessas crianças. Esses dados são compatíveis com as idéias de diversos autores (12)(13)(14)(15)(16) no sentido de que a consideração da perspectiva dos pais de crianças do espectro autístico quanto ao comportamento linguístico, cognitivo e social de seus filhos merece destaque, possibilitando que estes se tornem parceiros dos profissionais envolvidos no processo de intervenção, ajudando no monitoramento do nível de desenvolvimento destas crianças.…”
Section: Discussionunclassified
“…Entretanto, foi percebida a necessidade de uma análise e uma comparação dos mesmos aspectos, obtidos a partir da perspectiva de indivíduos que enxergam esse mesmo alvo, mas com outro foco, como as terapeutas (11) . A consideração da perspectiva dos pais de crianças do espectro autístico quanto ao comportamento linguístico, cognitivo e social de seus filhos vem sendo colocada em um lugar de destaque, uma vez que estes passam a ser parceiros dos profissionais envolvidos no processo de intervenção, ajudando no monitoramento do nível de desenvolvimento destas crianças (12)(13)(14)(15) . Investigando o uso da informação do contexto familiar para direcionar a avaliação e o processo terapêutico, observouse que o uso dessas informações em processos de avaliação e terapia não geram problemas, podendo contribuir para a estabilidade e durabilidade da redução de comportamentos desafiantes alcançados por meio de uma abordagem funcional da comunicação (16)(17)(18) .…”
Section: Introductionunclassified
“…However, this cut-off can be adapted for individual studies. Eaves et al (2006) found that sensitivity and specificity were lower for children with high verbal IQs, and it has been suggested that a lower cutoff may be appropriate (Corsello et al 2007). Thirty-one children were at cut-off point of 15 or above; six had scores from 9 to 13.…”
Section: Social Communication Questionnaire (Scq)mentioning
confidence: 99%
“…When only a combination of items with positive and significant Phi-values (although these individual values indicate weak associations) is used as in the shorter version of the SCQ, this would help improving the specificity (with sensitivity remaining above 0.80) as compared to using the complete instrument, especially for the age group 8-24 months. Somewhat similar suggestions for improving the SCQ have been put forward by Eaves et al (2006a). However, before the suggested alternatives can be used in clinical practice, these findings need to be replicated.…”
Section: Discussionmentioning
confidence: 88%